2018
DOI: 10.5430/jnep.v9n1p98
|View full text |Cite
|
Sign up to set email alerts
|

RN to BSN Students’ communication satisfaction with asynchronous discussion forums: Audio-video versus text-based responses

Abstract: Objective: This pilot study examined an innovative strategy for an RN to BSN online program, specifically focused on the required asynchronous discussion forums. The aim of the study was to compare RN to BSN students’ communication satisfaction with audio-video discussion responses versus the traditional text-based responses.Methods: Utilizing a pretest-posttest design, RN to BSN student’s communication satisfaction with traditional text-based discussion responses was measured using a 5-point Likert scale surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Although SP acts as an intervening variable of the CoI, it has been found to be “a necessary but not sufficient condition of a satisfying and effective online experience” (Swan et al, 2008, p. 8). This may explain why, in the previous quantitative study, students were significantly more satisfied, with asynchronous AV discussion responses being positive, accurate, and free flowing (Denson & Shurts, 2019).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although SP acts as an intervening variable of the CoI, it has been found to be “a necessary but not sufficient condition of a satisfying and effective online experience” (Swan et al, 2008, p. 8). This may explain why, in the previous quantitative study, students were significantly more satisfied, with asynchronous AV discussion responses being positive, accurate, and free flowing (Denson & Shurts, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…However, sparse literature was found that specifically investigated RN to BSN students’ experiences with AV discussion responses. To address the gap in knowledge, we conducted a quantitative study with RN to BSN students (Denson & Shurts, 2019), introducing the AV format within all course discussion forums; students had previously been exposed to traditional text-based discussions only. The findings revealed that - although students reported satisfaction with asynchronous AV discussion, with responses being positive, accurate, and free flowing, there was a decrease in SP when participating in the AV format.…”
mentioning
confidence: 99%